Natural Antioxidants as a Tool to Protect the Organs from Tumors Induced Ehrlich Ascites in Mice - Dalia I. Hemdan, Dina I. Hemdan (Pakistan Journal of Medical & Health Sciences, 2022)
The objective of this study was to estimate if pre-treatment with pomegranate or beetroot juice and their combination for EAC which induces tumor in mice has the antitumor effect. Therefore, antioxidant activity DPPH scavenging was determined. The organs liver, spleen, and kidney were weighted to body weight in mice injected with EAC and treated by cisplatin, pomegranate, beetroot, and both of each pomegranate and beetroot and compared with the mice normal group. Single-cell suspension from the spleen was determined and RNA was extracted from the liver using a total RNA isolation kit and mRNA gene expression in EAC Cells was quantitative Real-Time PCR (RT-qPCR) analysis. The results showed that the pomegranate and beetroot contained high amounts of phenolic acid and flavonoid compounds and the highest antioxidant activity, which gave the highest DPPH scavenging activity. Moreover, the changes in the organ weight of vital organs were determined and compared with the control group. Because homologous recombination appears a new objective for cancer treatment by pomegranate and beetroot juice as an alternative to anticancer drugs. Therefore, pomegranate and beetroot juice have antitumor and antiproliferative influences on the Ehrlich tumor. Therefore, the pomegranate or beetroot and their combination were homologous recombinations that sensitize cells to growth inhibition and apoptosis.